The Structure of Water in Silica Mesopores – Influence of the Pore Wall Polarity - Weinberger, Christian; Zysk, Frederik; Hartmann, Marc; Kaliannan, Naveen; Keil, Waldemar; Kühne, Thomas; Tiemann, Michael (Advanced Materials Interfaces)
In the spatial confinement of cylindrical mesopores with diameters of a few nanometers, water molecules experience restrictions in hydrogen bonding. This leads to a different behavior regarding the molecular orientational freedom (‘structure of water') compared to the bulk liquid state. In addition to the pore size, the behavior is also strongly affected by the strength of the pore wall-to-water interactions, that is, the pore wall polarity. In this work, this is studied both experimentally and theoretically. The surface polarity of mesoporous silica (SiO2) is modified by functionalization with trimethylsilyl moieties, resulting in a change from a hydrophilic (pristine) to a hydrophobic pore wall. The mesopore surface is characterized by N2 and H2O sorption experiments. Those results are combined with IR spectroscopy to investigate pore wall-to-water interactions leading to different structures of water in the mesopore. Furthermore, the water's structure is studied theoretically to gain deeper insight into the interfacial interactions. For this purpose, the structure of water is analyzed by pairing densities, coordination, and angular distributions with a novel adaptation of surface-specific sum-frequency generation calculation for pore environments.
Keywords: Mechanical Engineering; Mechanics of Materials

ℓ-torsion bounds for the class group of number fields with an ℓ-group as Galois group - Klüners, Jürgen; Wang, Jiuya (Proceedings of the American Mathematical Society)
We describe the relations among the ℓ-torsion conjecture, a conjecture of Malle giving an upper bound for the number of extensions, and the discriminant multiplicity conjecture. We prove that the latter two conjectures are equivalent in some sense. Altogether, the three conjectures are equivalent for the class of solvable groups. We then prove the ℓ-torsion conjecture for ℓ-groups and the other two conjectures for nilpotent groups.
Keywords: Applied Mathematics; General Mathematics

The asymptotics of nilpotent Galois groups - Klüners, Jürgen (Acta Arithmetica)
We prove an upper bound for the asymptotics of counting functions of number fields with nilpotent Galois groups.
Keywords: Algebra and Number Theory

Umformtechnisches Fügen von Stanzmuttern während des Formhärtens von 22MnB5 - Meyer, Sebastian

Pyrolysis of sucrose-derived hydrochar - Wortmann, Martin; Keil, Waldemar; Brockhagen, Bennet; Biedinger, Jan; Westphal, Michael; Weinberger, Christian; Diestelhorst, Elise; Hachmann, Wiebke; Zhao, Yanjing; Tiemann, Michael; Reiss, Günter; Hüsgen, Bruno; et al. (Journal of Analytical and Applied Pyrolysis)
The electrochemical properties of carbonaceous materials produced by hydrothermal carbonization, referred to as hydrochar, can be substantially improved by post-carbonization via pyrolysis. Although these materials have been widely studied for a variety of applications, the mechanisms underlying the pyrolysis are yet poorly understood. This study provides a comprehensive temperature-resolved characterization of the chemical composition, morphology and crystallinity of sucrose-derived hydrochar during pyrolysis. Thermogravimetric analysis, differential scanning calorimetry, and elemental analysis have shown that the dry hydrochar loses about 41% of its dry mass due to the exothermic disintegration of oxygen-containing groups until the carbonization is completed at about 850 °C with a total carbon yield of 93%. The carbonization and aromatization of the initially furanic and keto-aliphatic structure were analyzed by 13C solid-state nuclear magnetic resonance spectroscopy, X-ray photoelectron spectroscopy, and Fourier transform infrared spectroscopy. The transition from an amorphous to a nanocrystalline graphitic structure was analyzed using X-ray diffraction and Raman spectroscopy. The pore formation mechanism was examined by helium ion microscopy, transmission electron microscopy, and nitrogen adsorption measurements. The results indicate the formation of oxygen-rich nanoclusters up to 700 °C, which decompose up to 750 °C leaving behind equally sized pores, resulting in a surface area of up to 480 m2/g.
Keywords: Analytical Chemistry; Fuel Technology

Porous SiO2 coated dielectric metasurface with consistent performance independent of environmental conditions - Geromel, René; Weinberger, Christian; Brormann, Katja; Tiemann, Michael; Zentgraf, Thomas (Optical Materials Express)
With the rapid advances of functional dielectric metasurfaces and their integration on on-chip nanophotonic devices, the necessity of metasurfaces working in different environments, especially in biological applications, arose. However, the metasurfaces’ performance is tied to the unit cell’s efficiency and ultimately the surrounding environment it was designed for, thus reducing its applicability if exposed to altering refractive index media. Here, we report a method to increase a metasurface’s versatility by covering the high-index metasurface with a low index porous SiO2 film, protecting the metasurface from environmental changes while keeping the working efficiency unchanged. We show, that a covered metasurface retains its functionality even when exposed to fluidic environments.

Die Wahrnehmung lernförderlicher Faktoren digitaler Lernbegleitung während der Pandemie - Grosser, Christine; Bloh, Bea

Thermal neural networks: Lumped-parameter thermal modeling with state-space machine learning - Kirchgässner, Wilhelm; Wallscheid, Oliver; Böcker, Joachim (Engineering Applications of Artificial Intelligence)

Learning Thermal Properties and Temperature Models of Electric Motors with Neural Ordinary Differential Equations - Kirchgässner, Wilhelm; Wallscheid, Oliver; Böcker, Joachim (2022 International Power Electronics Conference (IPEC-Himeji 2022- ECCE Asia))

Der Marktplatz von Amazon - Eine wettbewerbspolitische Analyse - Kuzuoglu, Muhammed Numan

Transform the Internet: Why we Need a Public Service Internet - Fuchs, Christian; Unterberger, Klaus (Public Value Texte)

Continuous table tennis is associated with processing in frontal brain areas: an EEG approach - Visser, Anton; Büchel, Daniel; Lehmann, Tim; Baumeister, Jochen (Experimental Brain Research)
Abstract Coordinative challenging exercises in changing environments referred to as open-skill exercises seem to be beneficial on cognitive function. Although electroencephalographic research allows to investigate changes in cortical processing during movement, information about cortical dynamics during open-skill exercise is lacking. Therefore, the present study examines frontal brain activation during table tennis as an open-skill exercise compared to cycling exercise and a cognitive task. 21 healthy young adults conducted three blocks of table tennis, cycling and n-back task. Throughout the experiment, cortical activity was measured using 64-channel EEG system connected to a wireless amplifier. Cortical activity was analyzed calculating theta power (4–7.5 Hz) in frontocentral clusters revealed from independent component analysis. Repeated measures ANOVA was used to identify within subject differences between conditions (table tennis, cycling, n-back; p < .05). ANOVA revealed main-effects of condition on theta power in frontal ( p < .01, η p 2 = 0.35) and frontocentral ( p < .01, η p 2 = 0.39) brain areas. Post-hoc tests revealed increased theta power in table tennis compared to cycling in frontal brain areas ( p < .05, d = 1.42). In frontocentral brain areas, theta power was significant higher in table tennis compared to cycling ( p < .01, d = 1.03) and table tennis compared to the cognitive task ( p < .01, d = 1.06). Increases in theta power during continuous table tennis may reflect the increased demands in perception and processing of environmental stimuli during open-skill exercise. This study provides important insights that support the beneficial effect of open-skill exercise on brain function and suggest that using open-skill exercise may serve as an intervention to induce activation of the frontal cortex.
Keywords: General Neuroscience

Surface Instability Modulates Cortical Information Processing In Multi-Joint Compound Movements - Lehmann, Tim; Visser, Anton; Havers, Tim; Büchel, Daniel; Baumeister, Jochen (Medicine & Science in Sports & Exercise)
Keywords: Physical Therapy; Sports Therapy and Rehabilitation; Orthopedics and Sports Medicine

Effects of surface instability on cortical information processing during multi- joint compound movements: an exploratory EEG study - Lehmann, Tim; Visser, Anton; Havers, Tim; Büchel, Daniel; Baumeister, Jochen

Performance and Brain Activity in Older Adults while Playing Leaning and Stepping Exergames - Müller, Helen Martha; Skjæret-Maroni, Nina; Vereijken, Beatrix; Baumeister, Jochen

A combined flue gas cleaning system with a novel entrained flow SCR using an online synthesized catalyst (Poster) - Beimdiek, Janis; Schmid, Hans-Joachim
Keywords: clean air; harmful gas removal; denitrification; SCR; catalytic filtration; nanoparticles; flame-synthesis

Innovative Werkstoffherstellung für das Polymer Laser Sintern – Teil 2 - Rüther, Moritz Johannes; Klippstein, Sven Helge; Ponusamy, SathishKumar; Jesinghausen, Steffen; Schmid, Hans-Joachim (Werkstoffe)

Innovative Werkstoffherstellung für das Polymer Laser Sintern – Teil 1 - Rüther, Moritz Johannes; Klippstein, Sven Helge; Ponusamy, SathishKumar; Jesinghausen, Steffen; Schmid, Hans-Joachim (Werkstoffe)

Novel entrained flow SCR using online synthesized catalyst particles (Poster) - Beimdiek, Janis; Schmid, Hans-Joachim
Keywords: clean air; harmful gas removal; denitrification; SCR; catalytic filtration; nanoparticles; flame-synthesis

Continuous Situation-specific Development of Business Models: Knowledge Provision, Method Composition, Method Enactment - Gottschalk, Sebastian; Yigitbas, Enes; Nowosad, Alexander; Engels, Gregor (International Journal on Software and Systems Modeling (SoSyM))
The development of new business models is essential for startups to become successful, as well as for established companies to explore new business opportunities. However, developing such business models is a continuous challenging activity where different tasks need to be performed, and business decisions need to be made. Both have to fit the constantly changeable situation in which the business model is developed to reduce the risk of developing ineffective business models with low market penetration. Therefore, a method for developing situation-specific business models is needed. As a solution, we refine the concept of situational method engineering (SME) to business model development. SME, in turn, provides means to construct situation-specific development methods out of fragments from a method repository. We develop a concept for the continuous situation-specific development of business models based on design science. The approach uses the roles of a domain expert, a method engineer, and a business developer together with a repository with method fragments for developing business models and a repository with modeling artifacts for supporting the development. Both repositories are filled by utilizing the experience of domain experts. Out of these repositories, situation-specific development methods for developing business models can be continuously composed based on the changeable situation by the method engineer and enacted by the business developer. We implement it as an open-source tool and evaluate its applicability in an industrial case study of developing a business model for a local event platform. Our results show that situation awareness supports the continuous development of business models.
Keywords: Business Model Development; Situational Method Engineering; Situation-specific; Business Model Canvas; Continuous Development